Heavy thunderstorms on the Polish-German lowlands in the period 1951–2008 and their circulation conditions - Kolendowicz, Leszek (Quaestiones Geographicae, 2012)
The aim of the study was an analysis of the impact of atmospheric circulation over the territory of Europe on the frequency of occurrence of heavy thunderstorms on German Lowlands and on Polish Lowlands in the period 1951-2008. The atmospheric circulation in days with investigated phenomena was illustrated as the averaged image of the atmospheric pressure field over Europe (sea level pressure and 500 hPa geopotential heights). Heavy thunderstorm phenomena occur as a result of low pressure systems or low pressure troughs moving above investigated area and bringing cold air masses. Usually, the distribution of isobars at sea level indicates the occurrence of atmospheric fronts accompanying a low pressure system.